ANALYSIS OF THE EFFECT OF COMPETENCY AND INDEPENDENCE ON THE QUALITY OF AUDITED FINANCIAL STATEMENTS AUDIT RISK AS MEDIATION DURING THE COVID 19 PANDEMIC (Empirical Study on KAP in Central Java) - Dewi Saptantinah Puji Astuti; Aris Eddy Sarwono (Bajang Institute, 2022)
Cases of declining quality of audited financial reports in recent years have shown an increasing trend, supported by the existence of a pandemic condition with various obstacles faced by client companies, including financial difficulties, due to the impact of the pandemic, in such conditions the management is still required to account for the company's financial statements. The purpose of this study was to examine the effect of competence and independence on the quality of audited financial statements with audit risk as a mediating variable. This study uses a survey method with primary data sources, obtained by distributing questionnaires to respondents. The population in this study was auditors at Public Accounting Firms throughout Central Java, the sampling technique was purposive sampling. The results of the study using SEM PLS analysis showed that competence, independence and audit risk had a significant effect on the quality of audited financial statements, competence and independence had a significant effect on audit risk. While independence affects the quality of audited financial statements mediated by audit risk, while audit risk cannot mediate the effect of competence on the quality of audited financial statements. Suggestions for further research should be to expand the research sample and add variables that can affect the quality of audited financial statements such as the role of internal auditors.